STUDI SPEKTROSKOPI ELECTRON SPIN RESONANCE (ESR) LAPISAN TIPIS AMORF SILIKON KARBON (a-SiC:H) HASIL DEPOSISI METODE DC SPUTTERING - Rosari, Rosari (Makara Journal of Science, 2002)
The dangling bond defect density in sputtered amorphous silicon carbon alloys have been studied by electron spin resonance (ESR). The results show that the spin density decreased slightly with increasing methane fl ow rate (CH4 ). The infl uence of carbon and hydrogen incorporation on g-value revealed that for CH4 fl ow rate up to 8 sccm, the ESR signal is dominated by defects characteristic of a-Si:H fi lms and for CH4 fl ow rate higher than 8 sccm the g-value decreased towards those usually found in a-C:H fi lms. Infrared (IR) results suggest that as CH4 fl ow rate increases more carbon and hydrogen is incorporated into the fi lms to form Si-H, Si-C and C-H bonds. A direct relation between the IR results and the defect density and g-value is observed